(untitled) (Al-Academy, 2025)
Scenography, in all its forms, contains a large number of visual signs within the theatrical presentation system, in addition to the overlapping of the human senses that participate in its actual presence, due to the concepts, visions, and cultures that scenography includes, in addition to the aesthetic aspect, as the theatrical presentation is presented through a number of loaded signs, signs, and symbols. With direct and indirect connotations, through the elements of scenography of theatrical performance, and these and the aesthetics of these elements create opportunities for interpretation and communication. Therefore, scenography has a great impact in showing the formal structure in the historical theatrical space. Heritage and popular heritage contain a special world of imagination and perception that is a real background. For a living reality, the aesthetics of scenography derives from virtual worlds to form the environment of the historical show, and since the historical theatrical show requires accuracy in conveying its events to form an integrated work system, scenography exists within this system, and therefore the research problem is determined through this question (Have scenography been achieved in historical theater shows, and what does it carry? What are the meanings and connotations in the Arab theatrical performance, especially the research sample - the model - (Sidrat Al-Sheikh), an aesthetic function through exploitation of the popular inherited heritage in addition to its other psychological, semantic and dramatic functions? What effect did it have on the recipient’s culture? The current research aims to identify the aesthetics of scenography in historical theater performances by reviewing the network of mutual relationships between the historical theatrical performance system that relies on heritage and popular heritage. The researcher used the intentional method in selecting his research sample, which numbered (1), because this is a play that conforms to the requirements of the current research, which consists of the play (Sidrat Al-Sheikh) because it is one of the performances that imitates the Arab heritage through the idea of the text inspired by the novel (The White Sheikh) by His Highness Sheikh Sultan bin Muhammad Al Qasimi, Ruler of Sharjah. The most important results of the search are: 1-The Arab heritage and popular heritage present in the Arab countries have a prominent impact on the development of scenography in historical theater performances. 2- Historical theatre is an ancient art that aims to address people’s culture and nostalgia